(untitled) (Praxis Educativa, 2014)
This paper is about Jacques Derrida’s notios of “unbearable writings” and “experience-books”, words with which Michel Foucault names his own work. The idea of this crossing is to question the reduction of a text to logical analytical structures to combine teaching with the possibility of experience understood basically as a transformation. A way of understanding writing that turns into a proposal of essay.